Irishness troubles: trasformazioni dell'identità irlandese nella Field Day Theatre Company (Mantichora. Italian Journal of Performance Studies, 2020)
This paper analyzes the Field Day Theatre Company’s performances wondering whether we are confronted with an experience in a genuinely innovative way of looking at national identity or, rather, this is yet another way to state a different, but little hybrid, representation of Irishness.